HUBUNGAN SELF MANAGEMENT DENGAN KREATIVITAS BELAJAR SISWA SMP NEGERI 19 KOTA JAMBI - Ilham Prabowo; Rasimin Rasimin; Fellicia Ayu Sekonda (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2022)
Education has an important role in creating intelligent, creative, skilled, responsible, productive, and virtuous human resources. Education must pay attention to the potential of students by emphasizing efforts to develop student learning creativity optimally. The development of creativity requires the ability of students to do self-management because creativity arises from within each student, not something that comes from outside the student. This study aims to determine the level of student self-management, determine the level of student learning creativity, and analyze the significant relationship between self-management and student creativity at SMP Negeri 19 Jambi City for the 2020/2021 academic year. The approach used in this research is a quantitative approach with the type of correlational research. The population studied were students of Class VII and VIII of SMP Negeri 19 Jambi City, totaling 482 people. While the samples studied were 88 people. The instrument used is a questionnaire or questionnaire with five alternative answers. Analysis of the data used is product-moment correlation analysis. The results showed that the average score of the results of the measurement of the self-management variable of SMP Negeri 19 Jambi City students was 296.1 or 67.3%, the average score of the results of the measurement of student creativity at SMP Negeri 19 Jambi City was 268 or 60.9%, and the value of r calculated of 0.969. Based on the results of the study, it can be concluded that the student's ability to perform self-management is in a good category, and the students' learning creativity is in a good category. There is a very strong and significant positive relationship between self-management and the learning creativity of SMP Negeri 1 Jambi City students. This means that the higher the self-management of students, the higher the creativity of students' learning.